2015
DOI: 10.1080/03630242.2015.1118723
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a reformer Pilates program on body composition and morphological characteristics in active women after a detraining period

Abstract: The aim of this quasi-experimental pilot study was to explore the effects of a reformer Pilates program on the anthropometry, body composition, and somatotype of active adult women after a short non-exercise period. Twenty-eight women (mean age: 40.21 ± standard deviation of 8.12 years old) with one to three years of reformer Pilates experience participated in the study. The women participated in a reformer Pilates program for 16 weeks (one hour, twice per week) after 4 weeks of detraining (summer holidays) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
1
13
0
4
Order By: Relevance
“…Moreover, a research on triceps, subscapular, suprailiac, abdominal and thigh skinfolds found thigh as the largest one as well [45]. Furthermore, an examination of triceps, subscapular, biceps, iliac crest, suprailiac, abdominal, front thigh and medial calf showed front thigh as the largest one followed by abdominal [46]. Compared to these studies in non-athletes, participants had lower skinfold thickness in thigh (patella).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, a research on triceps, subscapular, suprailiac, abdominal and thigh skinfolds found thigh as the largest one as well [45]. Furthermore, an examination of triceps, subscapular, biceps, iliac crest, suprailiac, abdominal, front thigh and medial calf showed front thigh as the largest one followed by abdominal [46]. Compared to these studies in non-athletes, participants had lower skinfold thickness in thigh (patella).…”
Section: Discussionmentioning
confidence: 85%
“…(Lopes et al, 2017). While Lopes et al (2017) did not compare muscle mass between pre-and posttraining program, significant increases were observed for muscle mass after 16 weeks of reformer Pilates program (Vaquero-Cristóbal et al, 2016) as well as 16 weeks of mat Pilates program (Vaquero-Cristóbal et al, 2015). Meanwhile, there were studies of Pilates training in healthy subjects such as baseball players (English and Howe, 2007) and female dancers (Ahearn et al, 2018), but they did not measure muscle mass related variables.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, middle-aged women subjected to Pilates training did not show difference in body mass between the Pre and Post 4 week detraining periods [47]. On the other hand, the research of Gastebois and contributors observed that the same detraining period induces a significant change in body composition as evidenced by reduced lean mass and increased fat mass, despite any change in body weight [48].…”
Section: Discussionmentioning
confidence: 57%